The Development of Early Detection Tool for Stunting Prediction (Medico Legal Update, 2020)
Stunting is a nutritional problem in Indonesia which prevalence has experienced an increased every year.One way to overcoming nutritional problems, especially stunting, is the availability of technology, includingearly detection [tool] for prediction of stunting. The general objective of this research was to develop anearly detection tool for predicting stunting. This research was a cross-sectional study. This research wasconducted in Kendari and Semarang, from April to December 2019. The research population was childrenunder two years-old in Kendari and Semarang. The samples of this research were children under two yearsold in Kendari and Semarang. The data analysis was done using the SPSS program. The research results are:The prediction of stunting is formed when the maternal height variable is a predictive factor for stunting pv= 0.004 CI (1.573–11.438);shorter maternal height with a tendency of 4.242 times. Feeding is a predictivefactor for stunting pv = 0.047 CI (1.015–14.229); feeding to baby is only breast milk with a tendency of 3.800times. The maternal education is a predictive factor for stunting pv = 0.012 CI (1.153–3.225); lower maternaleducation with a tendency of 1.929 times. The use of drinking water is a predictive factor for stunting pv =0.027 CI (1.072–3.213); the use of unfiltered drinking water with a tendency of 1.858 times. The predictionof stunting is formed when the variable of maternal height is short, feeding to baby is only breast milk andmilk, Antenatal Care is lacking, maternal education is low, the drinking water used is unfiltered, the type oftoilet used is other than gooseneck toilet and the birth weight is LBW, thenthe prediction of stunting wouldbe 85%. Suggestions given in this research are that –from the models(variables) taken, namely inappropriatefeeding, inadequate ANC and low maternal education can predict stunting status thus it is necessary to makeimprovements to these variables.